Oysters in transition: hermaphrodite oysters display unique DNA methylation patterns in gill tissue - Sophie Valk; Marc Engelsma; Hendrik-Jan Megens; Pauline Kamermans; Albertinka J. Murk; Reindert Nijland (BMC Genomics)
Abstract Background European flat oysters (Ostrea edulis) are sequential hermaphrodites that alternate sex in response to environmental change. Epigenetics, including DNA methylation, are often involved in sex reversal through influencing gene transcription. Knowledge on the epigenetic mechanisms underlying sex reversal in hermaphrodite bivalves is limited to gonadal tissue and previous studies have only compared DNA methylomes of males and females. Therefore, the aim of this study is to assess whether sex-specific DNA methylation can be identified in somatic gill tissue of the flat oyster. Results By comparing whole-genome methylomes of 35 oysters of different sex phenotypes using nanopore sequencing, we demonstrate the presence of sex-specific DNA methylation patterns in somatic gill tissue. A total of 9,654 regions and 2,576 genes were differentially methylated between male, female, and hermaphrodite oysters. Functional analysis of differentially methylated genes indicated an association with energy homeostasis and metabolic processes, implying a remodeling of the energy balance. Conclusions This study is the first to characterize DNA methylomes of hermaphrodite oysters, providing new insights into the epigenetic mechanisms underlying sex reversal in a sequential hermaphrodite invertebrate. Additionally, this study characterizes sex-specific DNA methylation in somatic gill tissue, paving the way for non-lethal sex identification using epigenetic biomarkers.